Place and identity in William H. Gass' Middle C - Mäntykivi, Juuso (My University, 2019)
The thesis examines Middle C (2013) by the postmodern author William H. Gass and analyzes notions of place and identity in relation to the novel. The theoretical framework of the thesis relies on the definitions of place devised by humanistic geography from the 1970s onwards. The analysis presented in this thesis is based on the view that place and identity are intricately connected and mutually constitutive concepts. The thesis argues that the identities of the main characters in Middle C are shaped in relation to their experiences of the personally significant places they inhabit. The thesis is divided into four main sections. The first section is the introduction, which offers context and background to Gass and Middle C and clarifies the concepts of place and identity as they are understood in the thesis. The second section examines how the characters adapt to their changing environments by employing contextually desirable social roles. Particular attention is given to the protagonist Joseph Skizzen and how he manages to pass himself as an esteemed music professor despite lacking actual credentials for the position. The third section considers Joseph as a character and offers further analysis of the motivational factors underlying his behavior. Finally, the fourth section analyzes the significance of domestic places in the novel and how they are linked to the identity development of the characters.
Keywords: place, identity, role, postmodernism, home